1998
DOI: 10.1073/pnas.95.5.2492
|View full text |Cite
|
Sign up to set email alerts
|

HFE gene knockout produces mouse model of hereditary hemochromatosis

Abstract: Hereditary hemochromatosis (HH) is a common autosomal recessive disease characterized by increased iron absorption and progressive iron storage that results in damage to major organs in the body. Recently, a candidate gene for HH called HFE encoding a major histocompatibility complex class I-like protein was identified by positional cloning. Nearly 90% of Caucasian HH patients have been found to be homozygous for the same mutation (C282Y) in the HFE gene. To test the hypothesis that the HFE gene is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
295
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 489 publications
(329 citation statements)
references
References 26 publications
27
295
0
6
Order By: Relevance
“…Both mouse studies and, to a lesser extent, human studies indicate that, although heterozygous persons do show detectably higher levels of iron loading, their iron loading is not close to what would be expected for a haplotype insufficiency. 10,11 The protein levels of Hfe in Hfe ϩ/Ϫ mice as well as in the AAV-Hfe-transduced mice remain to be determined. HFE and TfR2 form a complex when expressed in tissue culture cells, leading to the hypothesis that they interact to form a sensor to detect the degree of Tf saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Both mouse studies and, to a lesser extent, human studies indicate that, although heterozygous persons do show detectably higher levels of iron loading, their iron loading is not close to what would be expected for a haplotype insufficiency. 10,11 The protein levels of Hfe in Hfe ϩ/Ϫ mice as well as in the AAV-Hfe-transduced mice remain to be determined. HFE and TfR2 form a complex when expressed in tissue culture cells, leading to the hypothesis that they interact to form a sensor to detect the degree of Tf saturation.…”
Section: Discussionmentioning
confidence: 99%
“…18 Abnormal LH pulsatile secretion may be associated with male infertility and could disrupt the regulatory role of both the Sertoli and Leydig cells, resulting in abnormal spermatogenesis. 19 To investigate the role of HFE in the regulation of iron homeostasis, Zhou et al 20 generated a knockout mouse model of HH by targeted disruption of the murine HFE gene. This study revealed that the HFE protein was involved in the regulation of iron homeostasis and that mutations in this gene were responsible for HH.…”
Section: Discussionmentioning
confidence: 99%
“…This Warburg metabolic pathway has therefore been proposed as a general anabolic principle of activated and proliferating cells, while glucose breakdown through oxidative phosphorylation is a characteristic of differentiated or resting cells – not only for tumours, but also in normal tissue and the immune system 26, 27. Indeed, in murine GM‐CSF‐DC (see below), Toll‐like receptor stimulation promotes increased anabolic glycolysis rather than oxidative phosphorylation, which is crucial for DC activation, survival and function in the face of increased membrane‐forming demands due to secretory processes or migration 28, 29, 30, 31. However, when 1,25‐OH‐VD3 is given to human monocytes undergoing GM‐CSF differentiation to create tolerogenic DC (as outlined above), an early transcriptional programme is started that engages oxidative phosphorylation 32, 33, 34.…”
Section: Vd3 In Metabolic Imprinting Of DCmentioning
confidence: 99%